Retribution Collection and Tellecomunication Tower Control on Increased Original Local Government Revenue in Banyuasin District - Sari, Novita; Noviardy, Andrian (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2024)
The aim of this research is to identify how retribution and control of telecommunications towers affect the increase in regional foreign income in Banyuasin Regency. The data sources in this research are secondary data, namely Surat Tanda Retribusi Daerah (STRD) and Surat Tanda Setoran (STS) at the Banyuasin Regency Diskominfo-SP. The research method used in this study is descriptive qualitative. There are three stages in this method: data condensation, data presentation, and verification or conclusions. The percentage of telecommunications tower control retribution collected by the Banyuasin Regency Government in 2020 has exceeded the revenue target, namely 100.23%, in 2021 it increased to 101.60%, while in 2022 it decreased to 84.89%. Even though there will be a decline in 2022, the realization of revenues in 2020 and 2021 has reached or even exceeded the targeted revenues. has been above 100%, this shows that the collection of telecommunications tower control retribution has been achieved very effectively. Meanwhile, the contribution of retribution and control of telecommunications towers to increasing PAD during 2020-2022 is still below 10%, so the criteria are very low.